Pengaruh Pemberian Inokulum Fungi Mikoriza Arbuskula (FMA) Campuran terhadap Kemunculan Penyakit Layu Fusarium pada Tanaman Mentimun (Cucumis sativus L.) dan Melon (Cucumis melo L.) - Nadya Sofia Siti Sa'adah; Uki Dwiputranto; Aris Mumpuni (Fakultas Biologi Universitas Jenderal Soedirman, 2021)
Cucumber (Cucumis sativus L.) and Melon (Cucumis melo L.) are examples of vegetables and fruit that are widely consumed by the community, and also have many benefits. The market demand for cucumbers and melons is very high. Therefore the production should meet the demand. There are several problems in production, and one of them is wilt caused by Fusarium. Conventionally, the use of synthetic fungicides is considering as the right solution for controlling fusarium wilt. However, taking into account the harmful effects of these fungicides, the use of Arbuscular Mycorrhizal Fungi (AMF) is a choice made. This study used a Completely Randomized Design (CRD) of mixed AMF inoculums (0, 5, 10, 15, 20 g FMA with zeolite/plant carrier medium). The main parameters observed were disease intensity, while the supporting parameters observed were pH, temperature, air humidity, disease incubation period, and degree of infection. The data obtained were analyzed using a Variety Test (F test) with a Standard Error of 5%. Based on the research result, plants which are inoculated by mycorrhizae inoculum is more resistant to fusarium wilt disease. The optimal dose of AMF mixture to reduce the intensity of fusarium wilt in cucumber (Cucumis sativus L.) plants is M3BT (AMF inoculation of 15 g / plant mixture), and melon (Cucumis melo L.) is M2BM (10 g / plant AMF mixture inoculation)